Neurocognitive development of the ability to manipulate information in working memory - Crone, Eveline A. (National Academy of Sciences, 2006)
The ability to manipulate information in working memory is a key factor in cognitive development. Here, we used event-related functional MRI to test the hypothesis that developmental improvements in manipulation, relative to pure maintenance, are associated with increased recruitment of dorsolateral (DL) prefrontal cortex (PFC) and superior parietal cortex. Three age groups (8–12 years old, 13–17 years old, and 18–25 years old) performed an object-working memory task with separate maintenance and manipulation conditions. We found that 8- to 12-year-olds did not perform the task as well as adolescents or adults, particularly on trials requiring manipulation in addition to maintenance. In this study, no age differences were observed in the activation profile of ventrolateral PFC, a region associated with online maintenance. In contrast, unlike the older participants, 8- to 12-year-olds failed to recruit right DL PFC and bilateral superior parietal cortex during the delay period for manipulation relative to maintenance. This group difference was observed specifically during the delay period, while participants reordered items in working memory, and could not be accounted for by group differences in performance. Across participants, activation levels in right DL PFC and superior parietal cortex, but not ventrolateral PFC, were positively correlated with performance on manipulation trials. These results indicate that increased recruitment of right DL PFC and bilateral parietal cortex during adolescence is associated with improvements in the ability to work with object representations.